2008
DOI: 10.1590/s0103-84782008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Influência da inoculação de rizóbios sobre a germinação e o vigor de plântulas de alface

Abstract: IIIInfluence of rhizobial inoculation on seedling vigor and germination of lettuce RESUMO Os rizóbios, conhecidos por sua capacidade de fixar N 2 em associação com leguminosas, também se mostram capazes de promover o crescimento de não-leguminosas, especialmente pela produção de ácido indol-acético (AIA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
19

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 14 publications
1
11
0
19
Order By: Relevance
“…Even though final germination rates were unaffected by rhizobial inoculation, the increase in initial germination rates promoted by those eight isolates led to an associated increase in the germination speed index. Earlier germination in bacterized seeds was also reported by Biswas et al (2000b), Gupta et al (2002), Pandey et al (2005) and Schlindwein et al (2008), and is an important factor for crop establishment. The increase in seedlings vigor is an important aspect in rice crops, because it may result in earlier seedling emergence, allowing rice seedlings to overcome weed competition (Gibson et al, 2002).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Even though final germination rates were unaffected by rhizobial inoculation, the increase in initial germination rates promoted by those eight isolates led to an associated increase in the germination speed index. Earlier germination in bacterized seeds was also reported by Biswas et al (2000b), Gupta et al (2002), Pandey et al (2005) and Schlindwein et al (2008), and is an important factor for crop establishment. The increase in seedlings vigor is an important aspect in rice crops, because it may result in earlier seedling emergence, allowing rice seedlings to overcome weed competition (Gibson et al, 2002).…”
Section: Resultssupporting
confidence: 53%
“…Indoleacetic acid production is frequently pointed out as one of the main mechanisms of plant growth promotion (Biswas et al, 2000a;Khalid et al, 2004;Chi et al, 2005;Lee et al, 2006). However, this positive effect depends on the amount of IAA produced by the bacterium, since an IAA overproduction is considered deleterious to plants (Barazani & Friedman, 1999;Ahmad et al, 2005;Schlindwein et al, 2008). Similarly to other phytohormones, IAA exerts a stimulatory effect on plant growth within a narrow concentration range only, outside of which the plant is either unresponsive or its growth is inhibited (Biswas et al, 2000b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the contribution of rhizobia to biological N fixation, it is known that these microorganisms act as plant growth promoters and are involved in actions such as phosphate solubilization (Marra et al, 2012), production of siderophores (Jin et al, 2006), and production of phytohormones (Schlindwein et al, 2008), among other effects, all mechanisms that facilitate establishment of plants in degraded environments. This may be the explanation for the growth stimulation promoted by isolates UFSC-B5 and M8 in maricá, where even with low nodulation percentages there was considerable plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Miransari and Smith (2014) pointed out that ethylene and gibberellins affect radicle growth, with gibberellins being the most important hormone. High concentrations of the auxine (IAA) could also be responsible for the lower radicle growth induced by Pf (24) and this effect has been previously reported (Schlindwein et al, 2008). Fargasová (1994) suggested that auxins in general possess herbicide action (at specific concentration ranges) and this could possibly be involved in the adverse effect observed on germination parameters.…”
Section: Effect Of Rhizobacteria Inoculation On Lettuce Seeds Germinamentioning
confidence: 87%